Arabic Language Learning Design Based on Student Islamic Boarding School - Suhaidi, Suhaidi (CV. Publikasi Indonesia, 2025)
This study aims to find out how the design of Arabic Language Learning at Mohammad Natsir Institute of Da’wah, inhibiting factors of learning Arabic, and the steps to overcome these obstacles. The research uses a qualitative approach. The data collection employs observation techniques, interviews, and documentation. Checking the validity of the data uses three techniques, namely the extension of the researcher's presence, observational persistence, and triangulation. For data analysis, three stages are used: data reduction, data presentation, and conclusion/verification. Based on the results of the analysis, the conclusions are as follows: First, the design of the students’ Arabic learning is applied from the first semester to the fourth semester, especially for the students of the first and second semesters who must focus on learning Arabic, so that Indonesian language courses are studied in the next semester. Second, the inhibiting factor of Arabic learning is that the initial ability of the students is still very low, and the core issue is that the resources who become the mobilizer and the figure in language have not been instrumental in building Arabic language skills. Thirdly, some steps have been taken, such as increasing the hours of Arabic lessons, specializing Arabic materials in the first and second semesters, classifying students by ability, providing additional materials to students with special needs, and making extracurricular programs, playing Arabic audio, and translating some announcements both spoken and written in Arabic.